Quo Vadis Perlindungan Korban Tindak Pidana Kekerasan Seksual di Indonesia - Iswari Karna, Ayu Mirah; Setiabudhi, I Ketut Rai (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023), 2023)
The purpose of this study is to find out and analyze the direction of legal regulation and political protection for victims of sexual violence in Indonesia Act Number 12 of 2022 concerning the Crime of Sexual Violence. The ideas of this research are motivated by the birth of the latest legislation regarding sexual violence which is associated with the phenomenon and challenges of its enforcement. The research method used is a normative legal research method with a statue approach and analitycal and conceptual approach, and uses legal analysis techniques, namely description techniques, evaluation techniques, and argumentation techniques. The results of this study indicate that in Indonesia Act Number 12 of 2011 concerning the Crime of Sexual Violence, protection has been formally regulated for victims of sexual violence, both direct and indirect protection. It also regulates several types of criminal acts which so far have not received adequate regulation. It is hoped that in the future there will be consistency in law enforcement to ensure protection for victims of sexual violence. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis arah pengaturan dan politik hukum perlindungan korban kekerasan seksual dalam Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual. Ide dan gagasan penelitian ini dilatarbelakangi lahirnya peraturan perundang-undangan terbaru mengenai kekerasan seksual yang dikaitkan dengan fenomena dan tantangan penegakannya. Metode penelitian yang digunakan adalah metode penelitian hukum normatif dengan pendekatan perundang-undangan dan pendekatan analisis dan konsep hukum dan menggunakan teknik analisis bahan hukum yaitu teknik deskripsi, teknik evaluasi, dan teknik argumentasi. Hasil dari penelitian ini menunjukkan bahwa dalam Undang-Undang Nomor 12 Tahun 2011 tentang Tindak Pidana Kekerasan Seksual secara formal telah diatur perlindungan bagi korban kekerasan seksual, baik perlindungan langsung maupun tidak langsung. Diatur pula beberapa jenis tindak pidana yang selama ini belum memperoleh pengaturan yang memadai. Diharapkan kedepan konsistensi penegakan hukum untuk menjamin perlindungan bagi korban kekerasan seksual.